HUBUNGAN KESIAPAN BELAJAR MATEMATIKA SISWA DENGAN HASIL BELAJAR PADA MATERI BANGUN DATAR - Syafii, Mohamad; Fauziyah, Yayah (IKIP Siliwangi, 2022)
The aim of this paper is to find out empirically the relationship between readiness to learn mathematics and mathematics learning achievement in grade VII MTs Al-Masthuriyah Jakamulya, South Bekasi. This study uses a descriptive method with a survey technique in the form of a correlation study. The sample was taken from class VII-3 consisting of 34 students with purposive sampling technique. The research results obtained indicate that there is a positive relationship or correlation between learning readiness and mathematics learning achievement. This can be shown by the correlation coefficient rxyÂ = 0,863 and the regression equation Â 3,11+1,02x is obtained. The coefficient of determination shows that r2= (0,863)2=0,7448, which means that the contribution of the influence given to the learning readiness variable on the learning outcome variable in mathematics is 74.48%. The conclusion of this study is that there is a positive relationship between students' readiness to learn mathematics and learning outcomes in the chapter related to rectangular shapes for 7th grade students of MTs Al-Masthuriyah Bekasi Selatan.